A logical analysis of the debate on Hao River. Issue 4 (2nd October 2022) - Hao, Xudong
ABSTRACT: The debate between Zhuangzi and Huizi has profound epistemological significance, however, the main body of their debate comprises logical inferences and refutations. Therefore, this paper mainly focuses on the logical aspects of the debate. Some scholars have suggested that Huizi's argument is self-contradictory; however, in fact, based on such evaluations of Huizi's argument, we can conclude that Zhuangzi's logic is also self-contradictory. By utilizing modern logical analysis tools, this study reveals what and how the propositions and inferences contained in the language of the debate are articulated accurately and strictly. Moreover, by elaborating on the implicit premises omitted by Zhuangzi and Huizi, the actual logical process of the debate can be restored, and the logical fallacy of clandestine change of argumentative issue are revealed. This study presents clear modern logic analysis of the debate; it can also provide a more reliable logical basis for the discussions of Zhuangzi and Huizi's related philosophical thoughts.